2014
DOI: 10.1521/jscp.2014.33.8.701
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Everyone Else's Highlight Reels: How Facebook Usage is Linked to Depressive Symptoms

Abstract: Two studies investigated how social comparison to peers through computer-mediated interactions on Facebook might impact users' psychological health. Study 1 (N = 180) revealed an association between time spent on Facebook and depressive symptoms for both genders. However, results demonstrated that making Facebook social comparisons mediated the link between time spent on Facebook and depressive symptoms for men only. using a 14-day diary design (N = 152), Study 2 found that the relationship between the amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
309
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(334 citation statements)
references
References 39 publications
16
309
0
9
Order By: Relevance
“…These negative feelings have a direct impact on the self-esteem of individuals. Social comparisons made using social networking sites such as Facebook makes the people feel worse about their lives and promotes negative well-being of individuals (Steers, Wickham, & Acitelli, 2014). As a result people end up having low self-evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…These negative feelings have a direct impact on the self-esteem of individuals. Social comparisons made using social networking sites such as Facebook makes the people feel worse about their lives and promotes negative well-being of individuals (Steers, Wickham, & Acitelli, 2014). As a result people end up having low self-evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Hargreaves and Tiggeman (2004) PASSIVE FB USE, COMPARISON ON FB, AND BODY DISSATISFACTION 10 showed that exposure to idealized appearance in mass media was related to increased body dissatisfaction among girls, but not among boys. On the other hand, other studies suggest that gender plays no significant role in the relationships between media use, social comparison, and body dissatisfaction (de Vries, Peter, de Graaf, & Nikken, 2016;Steers, Wickham, & Acitelli, 2014). For instance, de Vries et al (2015) found no support for a moderating role of gender in the association between SNS use and adolescents' body dissatisfaction.…”
Section: Gender Differencesmentioning
confidence: 95%
“…In doing so, they are confronted with more instances when they are prone to comparing themselves with others (Chou & Edge, 2012;Tandoc et al, 2015). These social comparisons have a significant associated with Facebook-related depression (Steers, Wickham, & Acitelli, 2014). Also, the degree of social anxiety has been discussed as a mediator of the effects of SNS use (Rauch, Strobel, Bella, Odachowski, & Bloom, 2013).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Tsitsika et al, 2014). For example, social comparisons have been found to mediate a relationship between Facebook usage and depression for men only (Steers et al, 2014). Additionally, one study found that females experience higher levels of psychosocial symptoms then males across all levels of SNS usage (Müller et al, 2016).…”
Section: Hypotheses Developmentmentioning
confidence: 99%